Locating Suitable Solid Waste Dumping Sites using Remote Sensing and GIS Techniques in Aba Municipal, South-Eastern Nigeria - Ike, Felix; Ogechi, Isaac Lillian; Chibunna, Babington John (European Journal of Applied Sciences, 2022)
In most cities of Nigeria, indiscriminate solid waste dumping sites have taken over roadways, clogging drainage systems and slowing traffic flow. Conditions arising from indiscriminate waste disposal can lead to contamination of the environment and outbreaks of diseases. The main objective of this study was to examine the existing and predict potential suitable areas for solid waste dumping in Aba municipal in South-eastern Nigeria. The data used for this study were Landsat image; elevation map, ground control point of existing solid waste dumping sites, and topographical sheets of the study area. The maps were prepared by overlay and multi-criteria thresholds of roads, settlement, slope and distance to stream, We found that that 65% of the solid waste dumping area located close to roads and clustered in densely populated areas around the city center The final predictive suitability map for locating solid waste dumpsites indicated that, 11.35sqkm (19.41%) is not suitable, 26.47sqkm (45.25%) is less suitable, 16.17sqkm (27.65%) is moderately suitable and 4.5sqkm (7.69%) is highly suitable for Solid waste disposal. The potential most suitable areas for solid waste dumping sites fall about 5000m west of Ariaria market and 10,000m south east of Umu Mba in Aba Municipal.